Factors affecting online buying behaviour among working women in PLUS Malaysia Berhad / Nor Ashikin Mohd Nor - Mohd Nor, Nor Ashikin (Faculty of Business and Management, 2019)
This study examines on the factors affecting buying behaviour in online shopping among employees of PLUS Malaysia Berhad (PMB). Online uying behaviour is a broad scope that encompasses many determinants but in this study, the researcher specifically focuses on five determinants which are perceived benefits, perceived risks, hedonic motivation, psychological factor and website quality. Data were collected from 100 respondents using convenience sampling. The information gathered were assessed using the Social Science Statistical Package (SPSS) version 22. Numerous studies such as reliability analysis, descriptive assessment, correlation of Pearson and multiple regression analysis have been converged using SPSS. The findings suggested that there is a favourable connection in online shopping between perceived benefits, perceived risk, hedonic motivation and psychological factor towards the purchasing behaviour of customers. However, there is no significant relationship between website design towards consumers’ buying behaviour in online shopping. Recommendation and direction for future studies were discussed in this study.